2016
DOI: 10.1021/acs.nanolett.5b05235
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum Capacitors for High Frequency Tunable Analog Applications

Abstract: Graphene quantum capacitors (GQC) are demonstrated to be enablers of radio-frequency (RF) functions through voltage-tuning of their capacitance. We show that GQC complements MEMS and MOSFETs in terms of performance for high frequency analog applications and tunability. We propose a CMOS compatible fabrication process and report the first experimental assessment of their performance at microwaves frequencies (up to 10 GHz), demonstrating experimental GQCs in the pF range with a tuning ratio of 1.34:1 within 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…reported a graphene quantum capacitor with optimized device structure and contact resistance, which was capable to operate at microwave frequencies. [ 23 ]…”
Section: Figurementioning
confidence: 99%
“…reported a graphene quantum capacitor with optimized device structure and contact resistance, which was capable to operate at microwave frequencies. [ 23 ]…”
Section: Figurementioning
confidence: 99%
“…where ξ = Z/Z 0 . Equations (23) and (22) show that the parameter matrix is symmetric due to S 11 = S 22 and S 21 = S 12 . Fig.…”
Section: Frequency Modulation and Phase Modulation Simulation Andmentioning
confidence: 99%
“…Moreover, the strength of the interband transition in doped graphene is above 30A/W near 632nm optical wavelength [22], because doped graphene can generate more photoelectron-photohole pairs. The quantum capacitors of graphene are widely used in radio frequency (RF) [23] and electro-optics fields [24]. Researchers found that the photon-generated carrier concentration is positively correlated with optical energy [25], and the quantum capacitors of graphene layer (GL) increased with the increase of carrier concentration [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…So, it should be safe to ignore both of these aspects in a precisely fabricated 2D layered structure, as long as it is void of defects and interfaces are atomically flat. It must be pointed out that these restrictions on fabrication can be experimentally challenging to achieve, and are studied thoroughly in a recent article to which the readers are being referred [67]. Also, the minimal quantum conductivity σ Q may ideally not be achievable due to the disorder effects and finite temperature [44].…”
Section: Charging Delaymentioning
confidence: 99%